Genetic contributions to transdiagnostic symptom dimensions in patients with major depressive disorder, bipolar disorder, and schizophrenia spectrum disorders - David, Friederike S.; Stein, Frederike; Andlauer, Till F. M.; Streit, Fabian; Witt, Stephanie; Herms, Stefan; Hoffmann, Per; Heilmann-Heimbach, Stefanie; Opel, Nils; Repple, Jonathan; Jansen, Andreas; Nenadić, Igor; et al. (Schizophrenia research, 2023)
Major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia spectrum disorders (SZ) exhibit considerable phenotypic and genetic overlap. However, the contribution of genetic factors to their shared psychopathological symptom dimensions remains unclear. The present exploratory study investigated genetic contributions to the symptom dimensions “Depression”, “Negative syndrome”, “Positive formal thought disorder”, “Paranoid-hallucinatory syndrome”, and “Increased appetite” in a transdiagnostic subset of the German FOR2107 cohort (n = 1042 patients with MDD, BD, or SZ). As replication cohort, a subset of the German/Austrian PsyCourse study (n = 816 patients with MDD, BD, or SZ) was employed. First, the relationship between symptom dimensions and common variants associated with MDD, BD, and SZ was investigated via polygenic risk score (PRS) association analyses, with disorder-specific PRS as predictors and symptom dimensions as outcomes. In the FOR2107 study sample, PRS for BD and SZ were positively associated with “Positive formal thought disorder”, the PRS for SZ was positively associated with “Paranoid-hallucinatory syndrome”, and the PRS for BD was negatively associated with “Depression”. The effects of PRS for SZ were replicated in PsyCourse. No significant associations were observed for the MDD PRS. Second, genome-wide association studies (GWAS) were performed for the five symptom dimensions. No genome-wide significant associations and no replicable suggestive associations (p < 1e−6 in the GWAS) were identified. In summary, our results suggest that, similar to diagnostic categories, transdiagnostic psychiatric symptom dimensions are attributable to polygenic contributions with small effect sizes. Further studies in larger thoroughly phenotyped psychiatric cohorts are required to elucidate the genetic factors that shape psychopathological symptom dimensions.
Online verfügbar: 16. Januar 2023, Artikelversion: 16. Januar 2023
Gesehen am 18.07.2024